Fourth Industrial Revolution and the Political Economy of Big Data - Prodanov, Hristo (Research Papers, 2018)
The aim of this research is to analyze politico-economic consequences of one of the main features of the Fourth Industrial revolution – the big data. For this purpose, several tasks are accomplished: the characteristics and trends of the change and use of big data are revealed; the consequences they have for economy, politics and entire public system are analyzed; social inequalities and contradictions from the introduction of big data and the need for regulation are considered; the changes in traditional statistics as a result of the big data use are also part of the analysis. Politico-economic approach is applied with the precondition that politics and economy are sub-systems of the rapidly changing as a result of the big data politico-economic system. This is a brand new and unusually fast-growing field, not studied in our literature. It has a significant practical implication in the context of the problematic situations various institutions face in the conditions of huge and rapidly changing flows of information that demand rapid and rational decisions of political and economic actors.